(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Islamic literature is one of the richest global literatures because of its high-level literary product in poetry and prose, and because the Arab Islamic nation converges in its goals, culture and moral values, and there are common factors that unite its writers, poets and thinkers, and this in turn reflects on the literary relations and their interaction in phenomena of mutual influence between these literatures Peoples. Since ancient times, the Arabs and the Persians had long-standing joint relations, and participation in the social and cultural life between the two nations at all times revealed the closest ties between them, and the resulting exchange of political systems, beliefs, customs, language, literature and culture. `The research dealt with the Arab-Persian literary links and their impact on Arabs and Persians from the emergence of Islam until the end of the Umayyad era, in order to shed light on the literary mutual influences between Arabs and Persians. The research consisted of several axes, including: The relations of Arabs and Persians before the emergence of Islam, to clarify aspects of the ancient relationship between Persian and Arab literature. The links of Arabs and Persians in early Islam and during the Arab-Islamic conquest of Persia, as the communication channels between them multiplied. And the effect of the religious factor and the embrace of Islam on these connections. And talking about the impact of Persian literature on Arab literature, which dealt with the stages of the development of the Persian language, and the most prominent manifestations of the influence of Persian literature on Arabic literature in the fields of poetry, prose, judgment and singing, and what the Arabs took from the Persians in terms of Persian words and vocabulary. And talking about the impact of the Arabic language on the Persian language and the manifestations of this influence, the reasons for the desire of the Persians to learn the